The Past, the Present, and the Future: A Qualitative Study Exploring How Refugees' Experience of Time Influences Their Mental Health and Well-Being - Sagbakken, Mette; Bregård, Ida M.; Varvin, Sverre (Frontiers in Sociology, 2020)
The experience of time has a decisive influence on refugees’ well-being and suffering in all phases of their flight experiences. Basic safety is connected both developmentally and in present life with a feeling of continuity and predictability. Refugees often experience disruption of this basic sense of time in their home country due to war, persecution and often severe traumatisation, during flight, due to unpredictable and dangerous circumstances in the hands of smugglers and after flight, due to unpredictable circumstances in asylum centres, e.g. extended waiting-time and idleness. These context-dependent disruptions of normal experiences of time may lead to disturbances in mental life and extreme difficulties in organising one’s daily life. This article is based on narrative interviews with 78 asylum seekers and refugees in asylum centres in Norway, exploring their experiences before, during and after flight. The distinction between abstract, chronological time and concrete time connecting situational experiences (daily activities such as daily rhythm of sleep and wakefulness), proved important for understanding how the experiences became mentally disturbing and how people tried to cope with this experience more or often less successfully. Prominent findings were loss of future directedness, a feeling of being imprisoned or trapped, disempowerment, passivity and development of a negative view of self, memory disturbances with difficulty of placing oneself in time and space, disruptions of relations and a feeling of loss of developmental possibilities. Some had developed resilient strategies, such as imagining the flight as a holiday trip, to cope with the challenges, but most participants felt deeply disempowered and often disorientated. The analysis pointed clearly to a profound context dependent time-disrupting aspect of the refugee experience. An insecure and undefined present made participants unable to visualize their future and integrate the future in their experience of the present. This was connected with the inherent passivity and undefined waiting in the centres and camps, and with previous near encounters with annihilation and death. A response was often withdrawal into passivity.